(untitled) (Research, Society and Development, 2022)
The aging of the Brazilian population has been occurring in recent decades. Due to the COVID-19 pandemic and the isolation measures imposed, the elderly showed many changes in their daily lives, losing a lot of social interaction and reducing their physical activity. The objective of this study was to evaluate the level of depression and pain complaints in the elderly in the city of Redenção-PA. A total of 73 elderly people with a mean age of 69.8 ± 6.4 years were investigated, 58.9% of which were female. The results found showed that 5.5% of the elderly have depressive symptoms (which are more common in elderly people who have already had a stroke or who are widowed). Regarding the presence of pain, 41 of the 73 elderly people reported chronic pain, which is more common among women. Few studies evaluate the elderly population in northern Brazil. The search for epidemiological data on this population is essential to define strategies that aim to improve the quality of life in this region.